Cosmos sulphureus: environmental bioindicator of diversity of bees (Acta Scientiarum. Animal Sciences, 2025)
Among the flowers most visited by bees in Brazil, those belonging to the Asteraceae family stand out, and one of them is the cosmos (Cosmos sulphureus). This study aimed to evaluate the frequency, profile of visits and the type of collection of bees in the flowers of the cosmos during the year. The relationship between bees and cosmos flowers was observed by counting the frequency of visits and of material (nectar and / or pollen) to be collected. The foraging behavior of different bee species was also evaluated. The visits of the most frequent bees took place between 7:00 am and 12:00 pm. Among the main species of bees that made visits to the cosmos, those of the Halictidade family were noticeable: Pseudaugochloropsis graminea and Augochlora sp., Megachile rotundata solitary bees and, to a lesser extent, Plebeia remota stingless bees, Trigona spinipes stingless bees and Xylocopa frontalis and X. griscenses carpenter bees. Sporadic visits by stingless bees Melipona scutellaris, M. subnida, Partamona helleri, Scaptotrigona sp., Nannotrigona testaceicornes and africanized honeybees Apis mellifera. The cosmos should be planted close to apiaries and meliponaries as a source of food for Africanized honey bees, stingless bees and solitary bees.